Efficacy and safety evaluations of anlotinib in patients with advanced non-small cell lung cancer treated with bevacizumab - Jiang, Fenge; Li, Junxia; Kong, Xiangshuo; Sun, Ping; Qu, Huajun (Frontiers in Pharmacology, 2022)
Objective: The purpose of this study is to evaluate the efficacy and safety of anlotinib in patients with advanced non-small cell lung cancer (NSCLC) who had previously received bevacizumab. Methods: The participants were histopathologically or cytologically diagnosed advanced NSCLC patients whose disease progressed after at least one type of systemic therapy and who had previously received bevacizumab treatment. The patients were on 3-week administration cycles, including 2 weeks on-treatment (12 mg anlotinib oral route, once a day) and 1 week off-treatment. The primary end point of the trial was overall survival (OS). The secondary end points were progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR) and safety. Results: As of the data collection deadline (31 March 2021), 30 patients were enrolled in the study and received anlotinib treatment. All patients were included in the data set except one, who withdrew their consent after the start of treatment. The median follow-up period was 12.1 months (range, 3.6–25.0 months), and 29 patients were included in the evaluation of the treatment. Of the 29 patients, no CR cases occurred. In total, three patients (10.2%) showed a PR, 21 (72.4%) had SD, and five patients (17.2%) had PD. The objective response rate (ORR) was 10.2% (3 of 29 patients), and the disease control rate (DCR) was 82.7% (24 of 29 patients). The median progression-free survival (PFS) was 5.6 months (95% CI, 5.0–6.1 months; Figure 2). The median overall survival (OS) was 10.6 months (95% CI, 9.4–11.8 months; Figure 3). The overall tolerance of the anlotinib treatment was high among the enrolled patients. No treatment-related grade four or five toxicities were observed. Of the 29 patients, one patient’s anlotinib administration was reduced to 8 mg/day due to hypertension and headache. Most adverse events (AEs) were grade one or two; the most common AEs were fatigue (51.7%), hypertension (41.3%), hand–foot syndrome (41.4%), anorexia (34.5%) and hypertriglyceridemia (34.5%). Conclusion: Anlotinib demonstrated favourable activity and manageable toxicity in NSCLC patients who were treated with bevacizumab previously.